Interaction between pratylenchus sefaensis, meloidogyne javanica and rotylenchulus reniformis in sole and mixed crops of maize and cowpea - Egunjobi, O.A.; Akonde, P.T.; Caveness, F.E. (1986)
A field experiment in Nigeria was set up to investigate how mixed cropping may affect the population dynamics of P. sefaensis, M. javanica and R. reniformis in soil and within roots of maize and V. unguiculata. Under maize and V. unguiculata respectively, P. sefaensis and M. javanica were 3 and 2 times as numerous as under the mixed crop. R. reniformis was 9 times more abundant under V. unguiculata than under maize alone. Mixed cultures significantly reduced soil numbers of P. sefaensis relative to maize monoculture and M. javanica and R. reniformis relative to V. unguiculata. There were fewer P. sefaensis and R. reniformis in V. unguiculata roots when grown under mixed culture, while R. reniformis inside maize roots increased under the system. M. javanica inhibited P. sefaensis penetration into the roots of V. unguiculata and maize more than did M. javanica with R. reniformis. P. sefaensis enhanced entry of R. reniformis into roots of both crops. Lowest yields of maize and V. unguiculata occurred with P. sefaensis and M. javanica respectively. Shoots, roots and plant heights of maize were reduced with P. sefaensis alone or in combination with M. javanica and/or R. reniformis. Similar reductions occurred with V. unguiculata receiving M. javanica alone or in concomitance. Yields of both crops were negatively related to populations of these nemtodes. It is suggested that mixed cropping systems could be used for the cultural control of nematodes in maize.